2016
DOI: 10.1073/pnas.1608888113
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic origin of surface melting on ice crystals

Abstract: Since the pioneering prediction of surface melting by Michael Faraday, it has been widely accepted that thin water layers, called quasi-liquid layers (QLLs), homogeneously and completely wet ice surfaces. Contrary to this conventional wisdom, here we both theoretically and experimentally demonstrate that QLLs have more than two wetting states and that there is a first-order wetting transition between them. Furthermore, we find that QLLs are born not only under supersaturated conditions, as recently reported, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

8
119
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 85 publications
(135 citation statements)
references
References 47 publications
(79 reference statements)
8
119
4
Order By: Relevance
“…These states are characterized by either a droplet of liquid forming directly on the surface of ice, as would be favored by the long-ranged forces, or a droplet of liquid forming on top of a thin liquid film, as would be favored by the short-ranged forces. Clear observations of both are provided in the study by Murata et al (2), and, importantly, hysteresis is found in transitioning between these two states. This hysteresis is postulated to occur due to the metastability afforded by a first-order phase transition.…”
mentioning
confidence: 81%
See 4 more Smart Citations
“…These states are characterized by either a droplet of liquid forming directly on the surface of ice, as would be favored by the long-ranged forces, or a droplet of liquid forming on top of a thin liquid film, as would be favored by the short-ranged forces. Clear observations of both are provided in the study by Murata et al (2), and, importantly, hysteresis is found in transitioning between these two states. This hysteresis is postulated to occur due to the metastability afforded by a first-order phase transition.…”
mentioning
confidence: 81%
“…Such droplets were visualized earlier by Elbaum et al (11) in the water vapor pressure, with simple physical modeling rooted in classical wetting theory, to propose a thermodynamic origin for these observations. Building on previous work by Elbaum and Schick (12), Murata et al (2) posit that droplets form due to long-ranged attractive interactions between ice and vapor. For thick liquid layers, longranged interactions in the form of dispersion forces dominate over molecular interactions and ultimately determine the wetting behavior of the premelted layer.…”
mentioning
confidence: 97%
See 3 more Smart Citations